Effect of water-soluble gummy fiber, water-insoluble neutral detergent fiber isolated from Syzygium cumini seeds on biliary and fecal bile acids and sterols in rats fed a high cholesterol diet - Madhuri A Agnihotri; Aqueel Khan (Universiti Kebangsaan Malaysia, 2015)
Background: Highly viscous water-soluble fibers present in plant materials have been shown to reduce serum levels of blood cholesterol and lipid levels in animals and human beings. The water-insoluble neutral detergent fibers had shown no significant hypocholesterolemic and hypolipidemic effects. Objective: Effect of water-soluble gummy fiber, water-insoluble neutral detergent fiber isolated from Syzygium cumini seeds on biliary and fecal bile acids and sterols in rats fed a high cholesterol diet Materials and Methods: Effects of cholesterol-supplemented and cholesterol-unsupplemented diets containing 6%, 12%, and 18% water-soluble gummy fibers and 2.25%, 5%, and 10% water-insoluble detergent fibers were studied in both normal and diabetic rats for 21 days Results: Significant increase in biliary content and fecal excretion of bile acids was observed in rats fed for 21 days on cholesterol-supplemented and cholesterol-unsupplemented diets containing 6%, 12%, and 18% water-soluble gummy fibers, but 2.25%, 5%, and 10% water-insoluble neutral detergent fibers isolated from Syzygium cumini seeds had no significant effect on the above parameters. Conclusion: The increased biliary content and fecal excretion of bile acids and sterols in our study suggest that the dietary water-soluble gunny fiber of S. cumini seeds may enhance the breakdown of cholesterol, leading to an increased conversion of cholesterol to bile acids and salts that are excreted in alimentary canal.